The Role of Cybersecurity Application in Achieving Competitive Advantage – Field study on staff at King Abdelaziz International Airport in Jeddah – - Alghamdi, Ohoud Ahmed; Almostadi, Walaa Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to identify the role of cybersecurity in achieving the competitive advantage through research and analysis of programs used by employees' beneficiaries and determine the role of cyber security in them and cover the scientific gap in this Sphere. The analytical descriptive approach was used, the survey was used to survey the research sample to collect data, and the Search from the administrative staff at King Abdul-Aziz International Airport in Jeddah where the selection was A simple random sample of (340) Employee and the most important results were obtained:The study showed that cybersecurity has a role to play in achieving competitive advantage as The results revealed Simple Linear Regression Analysis that The secrecy has a positive and significant role in achieving competitive advantage at King Abdul-Aziz Airport international value of a statistically significant positive regression coefficient of confidentiality variable (0.454) and identification coefficient (0.03); This shows that secrecy affects 3%, and showed that there are positive indicators that support the role of Privacy where it is clear from the results that the value of the regression coefficient of the privacy variable was (0.092-) It is a negative and statistically significant value and this shows an inverse relationship with a negative impact between Availability of privacy at King Abdul-Aziz Airport and achieve competitive advantage where it does not exceed The value of this effect is 1%, and revealed that there is a positive role for strengthening by the value of the gradient coefficient For the booster variable has reached (0.378) which is a positive and statistically significant value and this shows the presence of positive impact and that reinforcement as an independent variable affects approximately 12% competitive advantage, and the results of the study revealed that competitive advantage is achieved largely in King Abdul-Aziz International Airport where results of unidirectional contrast analysis showed ANOVA that there are statistically significant differences between the opinions of respondents on the role of privacy and the role of Enhancement in achieving competitive advantage at King Abdul-Aziz International Airport in Jeddah Due to different educational qualification, differences were found to be in favor of employees with a Bachelor's degree, results revealed that there are statistically significant differences between the opinions of individuals Sample about the role of privacy and the role of reinforcement in achieving competitive advantage at King Airport Abdul-Aziz International in Jeddah with different years of experience, this shows that practical experience has an impact on Achieve competitive advantageThe researcher recommends the following:1- The need to continue achieving a high level of cybersecurity at King Abdelaziz Airport in Jeddah through its dimensions (confidentiality, privacy, and reinforcement), as this is considered part of the national security of the Kingdom of Saudi Arabia, because information security has now become an integral part of The field of security sciences, and reviewing the defects in the privacy elements.2- The application of cybersecurity is of great importance through its dimensions, due to its connection with achieving competitiveness in the field of aviation services, in national airports, so that the information security of airports is achieved from the threat of electronic terrorism.3- Rehabilitation and training of King Abdelaziz International Airport in Jeddah on the use of electronic control devices related to the information security of the aircraft operating system or the protection of the data of passengers traveling as customers of airlines.4- Paying attention to developing digital infrastructure for information security and enhancing cybersecurity for King Abdelaziz International Airport in Jeddah, due to its positive role in achieving competitiveness.
Keywords: Cybersecurity; Competitive Advantage; Confidentiality; Privacy; Enhancement